Sistema de indicadores de innovación para medir su incidencia en la gestión del hotel Mantahost de la ciudad de Manta - Alcívar Cornejo, Ángel Narcilo (2021)
The objective of this work was to create a system of innovation indicators in the Mantahost hotel in the city of Manta. It was developed in four phases, starting with the diagnosis of innovation through cards and guides, it was mainly determined that the establishment has a good operational infrastructure. The management processes are characterized by being deficient, emphasizing the control function, as well as the introduction of innovations. In the second phase, through a literature review and interviews, a system of innovation indicators was developed based on the validated proposal of Alfonso (2021), and the factors of strength and weakness were determined as a background for the redesign of associated improvement strategies. The third phase involved the analysis of the impact of innovation on hotel management by means of competitive performance, correlations and the CM model, from which a low result of this index was obtained, in addition to this analysis of how its performance directly affects hotel management with a level valued between medium- high. The fourth stage included the post-innovation to the results obtained in the diagnosis and selection of an IM strategy according to its current performance, an improvement action plan is proposed, which will be developed in the identified innovation dimensions and will focus on the management of operations in the different areas of the hotel. The plan also includes those responsible, follow-up mechanisms and tools applied for improvement.